CORRELATIONS BETWEEN PARENTING STYLE WITH THE CHILD INDEPENDENCE AND THE SEVERITY LEVELS OF DENTAL CARIES IN SCHOOL-AGE CHILDREN (Study Of Elementary School Students In The Work Area Of Srondol Health Center, Banyumanik District, Semarang City) - Cherinita Hamida; Henry Setyawan Susanto; Sri Yuliawati; Mateus Sakundarno Adi (Jurnal Kesehatan Masyarakat (Undip), 2020)
ABSTRACTParenting is a series of interactions with children. The right parenting becomes a factor that determines children's independence. A good child's independence increases the ability to solve problems including health problems. Dental caries is a disease of oral tissue that affects many children. Dental caries can cause malnutrition and interfere with children's growth. The study aims to determine the relationship between parenting applied by parents with the independence of children and the severity of children's dental caries. The study involved 120 pairs of respondents of primary-school-age mothers and children in the working area of the Srondol health center selected based on Multi-stage sampling. The cross-sectional study design and data collected through interviews included the type of parenting, the level of independence of the child, and the severity of caries based on the results of the caries depth foundation. Data analysis uses the Spearman Rank Correlation test and the Strong Estimate (OR) relationship. The results of the study: independence level is very independent 43.3%. Most of the parents' respondents applied the democratic parenting approach which was 42.5%). The severity of media caries suffered the most by child respondents (46.7%). There is a relationship between parenting patterns of the child's level of independence (p = 0,000 and rho = 0.407) and the better the parenting category the better the level of children's independence. There is a relationship between parents and the severity of children's dental caries (p = 0,000 and rho=-0,376) The better the parenting category, the lower the severity of dental caries in children. There is a relationship between children's independence and caries severity (p = 0,000 and rho = -0,668). So from the research, it was concluded that there was a relationship between the pattern of parenting with the child's independence and the severity of the child's dental caries.